The strategic role of school principals in academic supervision based on ruang GTK and E-Kinerja - Anna Mulyana; Fajar Alamsyah (12 Waiheru, 2026)
This study aims to (1) examine the strategic role of school principals in improving the effectiveness of academic supervision in Vocational High Schools (SMK), (2) identify the utilization of teacher performance management platforms in the Ruang GTK and e-Kinerja in the academic supervision process, and (3) analyze supporting and inhibiting factors in the implementation of academic supervision based on digital platform integration. This study uses a qualitative approach, grounded in a literature review, drawing on a systematic review of relevant scientific sources, including reputable journals, academic books, and educational policy documents. The data analysis technique is carried out using a content analysis approach through the stages of data reduction, categorization, synthesis, and interpretation. The results of the study indicate that school principals play a strategic role as instructional leaders and agents of change, determining the success of digital-based academic supervision. The use of the Ruang GTK and e-Kinerja platforms enhances supervision by providing more systematic, transparent, and accountable teacher performance data. The integration of digital platforms enables continuous monitoring and evaluation and supports data-driven decision-making. However, the implementation of digital-based academic supervision still faces various challenges, such as limited digital competency, uneven technological infrastructure, and resistance to change. This study concludes that the success of digital platform-integrated academic supervision depends heavily on the principal's leadership capacity to manage change and to utilize technology optimally. Therefore, strengthening digital competency, sustainable policy support, and developing an integrated system are needed to improve the quality of academic supervision in vocational high schools. This research provides theoretical contributions to the development of digital-based educational management studies and practical implications for improving teacher performance and learning quality.